DIGITAL ENTREPRENEURSHIP CAPABILITIES FOR WOMEN-LED MICROENTERPRISES: AN INTEGRATIVE MODEL OF ACCESS, AGENCY, AND MARKET RESILIENCE - Diah Fatma Sjoraida; Nida Garnida Fitrianti (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual and integrative review develops a framework for inclusive digital entrepreneurship in micro, small, and medium enterprises. It addresses the problem that women-led microenterprises may gain access to digital markets while continuing to face unequal resources, limited networks, care responsibilities, platform dependence, and uneven digital confidence. Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, and resilience, the paper explains how contextual digital capability, entrepreneurial agency, trusted peer networks, platform diversification, adaptive business learning can be organized as mutually reinforcing routines. The proposed pathway moves from problem diagnosis and capability mapping to bounded experimentation, evidence review, resource reconfiguration, and learning retention. No primary survey, interview, experimental, administrative, or statistical data are claimed. The framework links these mechanisms to market access, owner confidence, income continuity, strategic autonomy, inclusive resilience and identifies managerial, institutional, and research implications suitable for resource-constrained enterprises.